Decision-Making on the Choice of a Way to Respond to Conflict Situations in Persons with Affective Disorders - V.G. Bulygina; O.D. Peeva; N.E. Lysenko (Психология и право, 2022)
In order to research the relationship between individual psychological characteristics and the decision-making process in the perception of acute conflict situations in persons with affective disorders, an empirical study was conducted. 39 people aged 19 to 55 years (M=24, SD=10.3) were examined, of which 67% were females. The main group consisted of persons with affective disorders (N=11), the comparison group were mentally healthy. The research looked into volitional, intellectual regulation and the choice of the method of reaction after the subjects were presented some video recordings of single and long-term acute conflict situations, as well as neutral situations. The diagnostic complex included: methods of “Verbal-color interference”, “Comparison of similar patterns”, questionnaires “Style of self-regulation of behavior”, “Methods of coping behavior”, “Melbourne Decision-making Questionnaire”, “Hospital Anxiety and Depression Scale” (HADS). The stylistic features of decision-making, self-regulation of behavior and ways of coping behavior in persons with affective disorders were highlighted. It was revealed that people with affective disorders tend to make impulsive decisions, prefer avoidance strategies and confrontation in acute conflict situations. Specific changes of volitional and intellectual regulation in persons with affective disorders depending on the presented situation are shown. It was concluded that in persons with affective disorders, the speed of choosing a response method is associated with the stylistic features of decision–making. The rigidity of cognitive style is associated with the stylistic features of self-regulation of behavior and coping behavior.